SPECIAL OIL SHOCKS AND THEIR ECONOMIC EFFECTS (IRAQI OIL SHOCKS AS A MODEL) - Adnan Hadi Jaaz Al-Shamri; Dr. Rajaa Abdullah Issa Al-Salem (Scholar Express Journals, 2022)
The study aims to identify the special oil shocks, which the Iraqi economy has been exposed to, after the oil shocks are defined and identified historically with research into their causes, and the special oil shocks are distinguished, which are oil shocks, that occurred for political reasons more than economic ones, and their impact is limited to the country or geographical region , They occur due to fluctuations in the movement of international oil prices, which often occur to imbalances either on the supply side or on the demand side. In its history, Iraq has been subjected to two special oil shocks, the first was at the beginning of the Iraq-Iran war in 1981, as Iraqi oil exports decreased significantly due to the war operations in the Arab Gulf, which is the most important export port for Iraqi oil, and the second occurred after, in 1991, after the issuance of a Security Council resolution: The international community imposed economic sanctions on Iraq, the most important of which was preventing the export of Iraqi oil, and because of the importance of oil revenues in the formation of the gross domestic product and the revenues of the large public budget, these two shocks had a severe impact on the Iraqi economy
Keywords: oil shocks; private; oil; revenues